2021
DOI: 10.1136/rapm-2020-102315
|View full text |Cite
|
Sign up to set email alerts
|

Pericapsular nerve group (PENG) block provides improved short-term analgesia compared with the femoral nerve block in hip fracture surgery: a single-center double-blinded randomized comparative trial

Abstract: BackgroundThe femoral nerve block (FNB) may be used for analgesia in hip fracture surgery. The pericapsular nerve group (PENG) block is a novel regional technique and may provide better pain reduction while preserving motor function, but these blocks have not been directly compared.MethodsIn a single-center double-blinded randomized comparative trial, patients presenting for hip fracture surgery received analgesia with either FNB or PENG block. The primary outcome measure was pain scores (Numeric Rating Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(155 citation statements)
references
References 24 publications
6
140
2
7
Order By: Relevance
“…The pericapsular nerve group (PENG) block is an ultrasound-guided approach, first described by Giron-Arango et al for the blockade of the articular branches of the femoral, obturator and accessory obturator nerves that provide sensory innervation to the anterior hip capsule [9,10]. It has been successfully used as an alternative regional anaesthesia technique for the management of acute pain after hip fracture [11,12], but its applications are expanding, suggesting a potential role for analgesia after elective hip surgery [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The pericapsular nerve group (PENG) block is an ultrasound-guided approach, first described by Giron-Arango et al for the blockade of the articular branches of the femoral, obturator and accessory obturator nerves that provide sensory innervation to the anterior hip capsule [9,10]. It has been successfully used as an alternative regional anaesthesia technique for the management of acute pain after hip fracture [11,12], but its applications are expanding, suggesting a potential role for analgesia after elective hip surgery [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the PENG block has been limited to a small number of randomized controlled trials and letters to the editor. 3 , 7 9 While all studies have reported similar findings of improved analgesia and increased preservation of quadriceps strength, much remains unknown about this new regional technique, such as the block duration, minimum effective volume for dosing, patient-related outcome measures, and effect on health economics. This further analysis was aimed to provide clarity regarding the block duration and length of time to hospital discharge readiness.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size calculation is described in the primary publication. 3 The a priori power calculation was performed using PASS V.14 software (NCSS LLC, Kaysville, UT, USA) on the basis of the pain score reduction as the primary outcome in our previous analysis. This analysis showed mean reductions of 3.4 points after FNB and 7 points after PENG block (both out of 10) on day 0 postoperatively (standard deviation (SD) 2).…”
Section: Methodsmentioning
confidence: 99%
“…The Tissue Plane DOI: http://dx.doi.org/10.5772/intechopen.99533 reports and recently a randomised controlled study in the hip fracture population [101]. Whilst it appears remarkably effective for analgesia for hip fractures, the reasons for this are yet to be fully answered.…”
Section: The Modern Era Of the Tissue Plane In Regional Anaesthesiamentioning
confidence: 99%